2007
DOI: 10.1292/jvms.69.1263
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Antigen-Specific Immunoglobulin G Production in Mice by Co-Administration of L-Cystine and L-Theanine

Abstract: ABSTRACT. Supplementation with both cystine and glutamic acid increases the synthesis of glutathione (GSH), which has a marked effect on immune cell function, as compared with supplementation with either amino acid alone in human macrophages in vitro. As dietary glutamic acid is metabolized during intestinal transport, oral administration of L-theanine (γ-glutamylethylamide), which is metabolized to glutamic acid mainly in the liver, may act as a glutamic acid donor in vivo. The present study was performed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 30 publications
(33 reference statements)
2
51
1
Order By: Relevance
“…L -Cystine and L -theanine enhanced the antigen-specific anti-DNP IgM and IgG antibody titers in the serum at a lower dose (16 mg/kg) in 24-month-old C3H/HeN mice than in 12-week-old BALB/c mice (280 mg/kg) [22]. Franklin et al have reported that the peak GSH-induced proliferation is consistently fourfold greater in splenocytes from old rats as compared to young rats when cells are stimulated with concanavalin A.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…L -Cystine and L -theanine enhanced the antigen-specific anti-DNP IgM and IgG antibody titers in the serum at a lower dose (16 mg/kg) in 24-month-old C3H/HeN mice than in 12-week-old BALB/c mice (280 mg/kg) [22]. Franklin et al have reported that the peak GSH-induced proliferation is consistently fourfold greater in splenocytes from old rats as compared to young rats when cells are stimulated with concanavalin A.…”
Section: Discussionmentioning
confidence: 90%
“…Previously, we reported that combined oral administration of L -cystine and L -theanine induces significant enhancement of antigen-specific anti-DNP IgG antibody production in 12-week-old BALB/c mice [22]. It has been reported that antigen-specific anti-DNP IgG antibody production in female C3H/HeN mice decreases with age [35].…”
Section: Enhancement Of Antigen-specific Igm Antibody Production By Cmentioning
confidence: 92%
See 3 more Smart Citations